Argumentação em atividades de modelagem matemática - Tonello, Tancredo Heriberto (2017)
Modeling in mathematics education has been developing significantly over the last forty years. Even so, it has not yet arrived significantly in schools, probably due to limitations in the modeling training of educators, the lack of time for class preparation, or the lack of studies that show the type of knowledge taught and how it contributes effectively to the learning of Mathematics. The present work intends to contribute in this sense, investigating the types of arguments that are present in the teaching activities of Mathematics with modeling in the Basic School. Two types of activities were created: mathematical instruction and modeling, in order to review contents and solve real problems, respectively. The application occurred in a second year high school class. A framework with language and argumentative categories was developed and used to analyze students' statements in assessments or annotated in logbooks. It was observed that the types of languages and arguments depend on the way of conducting didactic activities, that in the modeling process the most frequent types of argumentation are those based on references (previous experiences, people and books) and that the deductive and generalization tend to compose the final stage of the argumentation process.